Islam dalam Lembaga Negara: Analisis Tafsir Maudhu’i - Dzul Adli Mudzoffar Al Arifi; Evan Raif; Fatur Rahmat Saifullah Tawil; Hikmawan Akbar; Asep Abdul Muhyi (UIN Sunan Gunung Djati Bandung, 2023)
The purpose of this research is to study more broadly related to state institutions and Islam. This study used a qualitative method with data collection using the maudhu'i interpretation method. The formal object of research is about the science of interpretation. The material object is a state institution in QS. Saba verse 15 and QS. Al-balad verses 1 and 2. The results of the discussion of this study are that the verses studied through the perspective of maudhu'i interpretation have a clear basis for explaining to the people and can be practiced. This research concludes that QS. Saba verse 15 and QS. Al-balad verses 1 and 2 are relevant for use as a basis for practice in state institutions.